Comparative reactivity studies of dppf-containing CpRuII and (C6Me6)RuII complexes towards different donor ligands (dppf=1,1′-bis(diphenylphosphino)ferrocene) - Lu, X.L. (2014)
10.1016/j.jorganchem.2004.03.022